Pengaruh Penambahan Bottom Ash Sebagai Bahan Stabilisasi Tanah Gambut Terhadap Nilai CBR - Mega Sukma Rismawati; Mega Sukma Rismawati (Universitas Teuku Umar, 2022)
Soil is the basic material used to support the planning of civil construction buildings. If a construction is built on soil conditions that have low bearing capacity, it will cause problems during construction. One type of soil that has a low bearing capacity is peat soil. Therefore it is necessary to improve the type of soil that has a low soil bearing capacity, namely peat soil by using the soil stabilization method. The purpose of this study was to determine the effect of adding 15%, 20%, 25%, 30% coal bottom ash with a curing period of 0 days and 7 days in terms of the CBR value. Based on the research that has been done, it is found that the more addition coal bottom ash with a curing time of 0 days and 7 days, the CBR value of the soil will increase. The CBR values obtained from testing in the laboratory are 2.43% and 3.91%, where based on the results of these tests there is an increase in the CBR value with the addition of 30% coal bottom ash with a curing period of 7 days.